2023
DOI: 10.1007/s10815-022-02711-w
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted hatching improves pregnancy outcomes in frozen-thawed embryo transfer cycles of cleavage-stage embryos: a large retrospective cohort study with propensity score matching

Abstract: Introduction Laser-assisted hatching (LAH) is a commonly used adjunct technique; however, its effectiveness has not been fully established. Objective We evaluated the effects of LAH on pregnancy outcomes in frozen-thawed embryo transfer (FET) cycles of cleavage-stage embryos. Materials and methods This retrospective study involved 5779 FET cycles performed at the Reproductive and Genetic Center in the Affiliated Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The decision to transfer one or two embryos was made by the clinician prior to the procedure. Vitri ed embryos were thawed on the morning of the transfer day, following procedures outlined in previous reports [21] .…”
Section: Ovarian Stimulation and Laboratory Protocolsmentioning
confidence: 99%
“…The decision to transfer one or two embryos was made by the clinician prior to the procedure. Vitri ed embryos were thawed on the morning of the transfer day, following procedures outlined in previous reports [21] .…”
Section: Ovarian Stimulation and Laboratory Protocolsmentioning
confidence: 99%
“…Finally, two recent studies again reported divergent findings. Wei and colleagues analysed 3,535 FETs, out of which 2,297 were non-AH cycles and in 1,238 laser AH was applied (Wei et al, 2023). Their results found a higher LBR in the AH group compared to the non-AH group (34.9% versus 31.4%, p = 0.024).…”
Section: Blastocyst Shrinkage Before Vitrification and Assisted Hatch...mentioning
confidence: 99%
“…Significantly, LAH appears more effective in enhancing pregnancy rates than chemical acidification [ 14 ]. Furthermore, frozen embryos subjected to LAH exhibit notably higher live birth rates than those no-LAH [ 15 ].…”
Section: Introductionmentioning
confidence: 99%